1983
DOI: 10.1073/pnas.80.17.5185
|View full text |Cite
|
Sign up to set email alerts
|

39K, 23Na, and 31P NMR studies of ion transport in Saccharomyces cerevisiae.

Abstract: The relationship between efflux and influx of K+, Na', and intracellular pH (pH' ) in yeast cells upon energizing by oxygenation was studied by using the noninvasive technique of -9K, DNa, and 31P NMR.spectroscopy. By introducing an anionic paramagnetic shift reagent, Dy3+(P3O)2i, into the medium, NMR'signals of intra-and extracellular K+ and Na+ could be resolved, enabling us to study ion transport processes by NMR. Measurements showed that 40% of the intracellular K+ In this work we studied by the noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 23 publications
6
40
0
Order By: Relevance
“…Until the 23Na NMR method was applied to the Na' analyses in cells, analyses were restricted to the cellassociated ions, and the bound or attached sodium content was not distinguished (Ogino et al, 1983;Gilboa et al, 1991). According to our analyses, the concentrations of free and bound sodium in the cytosol were 0.13-0.14 and 0.23-0-26 pmol (mg protein)-', respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Until the 23Na NMR method was applied to the Na' analyses in cells, analyses were restricted to the cellassociated ions, and the bound or attached sodium content was not distinguished (Ogino et al, 1983;Gilboa et al, 1991). According to our analyses, the concentrations of free and bound sodium in the cytosol were 0.13-0.14 and 0.23-0-26 pmol (mg protein)-', respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The observation of separate signals for intra-and extracellular Na+ and K+ as shown in Figs. 2 and 3 enabled us to determine directly their NMR visibility in RBC without physically isolating the intra-and extracellular compartments by inducing ion fluxes and comparing the changes in the NMR signals of intra-and extracellular Na" and K+ (11). In this experiment, RBC were resuspended into a Na'-free choline buffer at 250C and an ionophore, gramicidin (15 Na' were plotted against those of the extracellular Na' (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A with our home-built solenoidal coil probe (11). During the NMR measurements, the cells were oxygenated and gently mixed with a propeller driven by an air turbine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 (spectra C and D) showed that after lysis of the cells, there was, with time, a progressive downfield shift in the resonance attributable to the external sodium ions. This timedependent downfield shift observed upon lysis of the cells is believed to be the result of hydrolysis of the shift reagent by the released intracellular phosphatases (26). Thus, in these studies, downfield shifts in the external sodium resonances were taken to be indicators of cell lysis.…”
Section: Methodsmentioning
confidence: 99%